Soil respiration dynamics in Cinnamomum camphora forest and a nearby Liquidambar formosana forest in Subtropical China - Tian, DaLun; Wang, GuangJun; Yan, WenDe; Xiang, WenHua; Peng, ChangHui (Chinese Science Bulletin, 2010)

Variation in runoff with age of Chinese fir plantations in Central South China - Tian, Dalun; Yan, Wende; Chen, Xiaoyong; Deng, Xiangwen; Peng, Yuanying; Kang, Wenxing; Peng, Changhui (Hydrological Processes, 2008)
Abstract To determine the influence of forest structures on runoff characteristics, the hydrological effects of Chinese fir plantations were studied by analysing runoff patterns at different growth and development stages (stand age classes I to V) from 1984 to 2004 at the Huitong Ecosystem Research Station, Central South University of Forestry and Technology, Hunan Province, Central South China. Results for two small experimental Chinese fir watersheds showed different peak values for surface runoff amount and coefficients at different ages, with lowest values in age classes I and V and highest values in age classes II and III. However, both underground and total runoff coefficients decreased with increasing age class. Total runoff coefficient was about twice as high in age class I (30·8%) as that in age class V (15·8%). Higher underground and total runoff coefficients were found in young forests. This was mainly attributed to soil disturbance due to human management practices such as site ploughing. Results indicate that Chinese fir plantations play a significant role in regulating water distribution in the watershed. Useful information is provided on the effects of forest management practices on hydrological processes in forest plantations. Copyright © 2008 John Wiley & Sons, Ltd.

Heavy metal accumulation by panicled goldenrain tree (Koelreuteria paniculata) and common elaeocarpus (Elaeocarpus decipens) in abandoned mine soils in southern China - Tian, Dalun; Zhu, Fan; Yan, Wende; Xi, Fang; Xiang, Wenhua; Deng, Xiangwen; Wang, Guangjun; Peng, Changhui (Journal of Environmental Sciences, 2009)

Applying an artificial neural network to simulate and predict Chinese fir (Cunninghamia lanceolata) plantation carbon flux in subtropical China - Wen, Xuding; Zhao, Zhonghui; Deng, Xiangwen; Xiang, Wenhua; Tian, Dalun; Yan, Wende; Zhou, Xiaolu; Peng, Changhui (Ecological Modelling, 2014)